2022
DOI: 10.20525/ijrbs.v11i4.1839
|View full text |Cite
|
Sign up to set email alerts
|

The effect of entrepreneurial mindset, work environment on employees' work performance

Abstract: The study aims to examine the effect of the entrepreneurial mindset and work environment the individual work performance. To deepen the understanding of the concepts and establish the theories of the study, literature was reviewed. The study used a descriptive assessment and correlation research design. Total enumeration sampling was taken as the sampling design of the study. Therefore, the population of the study was all employees of Divine Word College of Laoag, a total of 169 employees. Questionnaires were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Employees value work as full of meaning and purpose, and employees are always focused at work (Yu et al, 2020). In such a way, if it is supported by a comfortable physical work environment, such as equipment that supports work, proper lighting, equipment, the right workspace temperature, comfortable and attractive decorations, and a workspace that is not noisy (Ajiardani & Anjaningrum, 2022;and Wu et al, 2021), it will be easy for employees to behave innovatively which ultimately improves performance as found by Ajiardani & Anjaningrum (2022), Andriyanty et al (2021), and Kim et al (2019) who revealed the work engagement strong influence on IWB which then has a positive impact on the resulting performance (Ajiardani & Anjaningrum, 2022;Abun et al, 2022;Novitasari & Iskandar, 2022). Employees who are strongly involved in work are a business strategy tool in this era because if employees are physically and mentally maintained, the company can survive and overcome competition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Employees value work as full of meaning and purpose, and employees are always focused at work (Yu et al, 2020). In such a way, if it is supported by a comfortable physical work environment, such as equipment that supports work, proper lighting, equipment, the right workspace temperature, comfortable and attractive decorations, and a workspace that is not noisy (Ajiardani & Anjaningrum, 2022;and Wu et al, 2021), it will be easy for employees to behave innovatively which ultimately improves performance as found by Ajiardani & Anjaningrum (2022), Andriyanty et al (2021), and Kim et al (2019) who revealed the work engagement strong influence on IWB which then has a positive impact on the resulting performance (Ajiardani & Anjaningrum, 2022;Abun et al, 2022;Novitasari & Iskandar, 2022). Employees who are strongly involved in work are a business strategy tool in this era because if employees are physically and mentally maintained, the company can survive and overcome competition.…”
Section: Discussionmentioning
confidence: 99%
“…Employee performance was also found to be dominated by the physical work environment (Ajiardani & Anjaningrum, 2022;Abun et al, 2022;and Novitasari & Iskandar, 2022). The physical work environment is a requirement that must be addressed because it lets employees do their job optimally even though certain conditions, such as stressful conditions, reduce performance.…”
Section: Work Engagement Physical Work Environment Innovative Work Be...mentioning
confidence: 99%
“…They also prioritize sincerity and commitment to their work (Bataineh, 2020). Additionally, they feel motivated by job satisfaction and increased responsibility (Abun et al, 2022;Ani et al, 2021). These findings underscore the significance of work ethics in driving employee performance.…”
Section: Composite Mean 432 A/h Overall Mean 415 A/hmentioning
confidence: 99%
“…According to the results, there is a strong correlation between participation in entrepreneurial education activities and both entrepreneurial intent and action. Abun et al (2022) studied the link between an entrepreneurial frame of mind and a productive workplace and found significant association. Also, Momodu et al (2019) looked into the manufacturing of polyurethane as a test case for greening Nigeria's economy for industrial and environmental sustainability, and their results showed that an entrepreneurial attitude and a happy work environment favorably improve workers' job performance.…”
Section: Entrepreneurial Mindset Entrepreneurial Competence and Organ...mentioning
confidence: 99%